2001
DOI: 10.1021/jo016013s
|View full text |Cite
|
Sign up to set email alerts
|

Selective Oxidation of Allylic Sulfides by Hydrogen Peroxide with the Trirutile-type Solid Oxide Catalyst LiNbMoO6

Abstract: Chemoselective sulfur oxidation of allylic sulfides containing double bonds of high electron density due to multiple alkyl substituents or extended conjugation was developed using the composite metal oxide catalyst, LiNbMoO(6), without any epoxidation of the electron-rich double bond(s). Selective oxidation to either the corresponding sulfoxides or the sulfones was realized by controlling the stoichiometry of the quantitative oxidant, H(2)O(2). This new oxidant system had general applicability for chemoselecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
40
0
1

Year Published

2002
2002
2019
2019

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 70 publications
(41 citation statements)
references
References 34 publications
0
40
0
1
Order By: Relevance
“…The amount of thioanisole sulfoxide produced was monitored by HPLC. As reported in the Table 1, HNbMoO 6 , LiNbMoO 6 and HNbWO 6 showed excellent catalytic activities. Though the oxidations were completed after 3 hr (entry 1-3), more than 90% of thioanisole was oxidized to its sulfoxide within 1hr.…”
mentioning
confidence: 55%
See 1 more Smart Citation
“…The amount of thioanisole sulfoxide produced was monitored by HPLC. As reported in the Table 1, HNbMoO 6 , LiNbMoO 6 and HNbWO 6 showed excellent catalytic activities. Though the oxidations were completed after 3 hr (entry 1-3), more than 90% of thioanisole was oxidized to its sulfoxide within 1hr.…”
mentioning
confidence: 55%
“…5 However, the catalytic activity of the oxide in organic reactions has not been well studied in spite of the potentials expected from the two different transition metals contained in the solid oxide. Recently, we reported a selective sulfoxidation of allylic sulfides catalyzed by the trirutile-type solid oxide, LiNbMoO 6 6 and successfully applied the oxidation method to the synthesis of Lansoprazole. 7 Because of the good catalytic activity shown by the LiNbMoO 6 in the sulfoxidation of sulfides, we decided to test other trirutile-type solid oxides, AMM'O 6 (A=H, Li, M=Nb, Ta, M'=Mo, W), as a catalyst in the hydrogen peroxide oxidation of sulfides to sulfoxides (Eq.…”
mentioning
confidence: 99%
“…The reaction mixture was diluted with dichloromethane and washed with saturated NaHCO 3 and brine. The organic layer was dried over MgSO 4 , filtered and concentrated in vacuo to afford 245 mg (91%) of 8: …”
Section: -Chloromethyl-3-methyl-4-(222-trifluoroethoxy)pyridine (8)mentioning
confidence: 99%
“…3 Recently, we found that trirutile type solid oxides catalyze the hydrogen peroxide oxidation of sulfides to sulfoxides very efficiently. 4 The reaction was very selective producing sulfoxide with negligible amount of sulfone. Since the reaction is performed under heterogeneous conditions, the solid catalyst can be easily recovered by a simple filtration of the final reaction mixture.…”
mentioning
confidence: 99%
“…It is also this difference in anion-stabilizing ability that makes sulfone a better leaving group than sulfide, and, thus, chemoselective base-promoted dehydrosulfonation reactions of 6 proceeded to bring two isolated CC bonds into conjugation, producing the allylic sulfides 7a ± 7c with a conjugated triene moiety. Chemoselective oxidation of sulfur was then accomplished by the LiNbMoO 6 ÀH 2 O 2 oxidant system [12], without any oxidation of the CC bonds, to produce the desired allylic sulfones 2a ± 2c containing conjugated triene moieties.…”
mentioning
confidence: 99%